Applications of operational research and mathematical models in management - Miltiadis Chalikias (MDPI, 2020)
This book, Applications of Operational Research and Mathematical Models in Management, includes all the papers published in the Mathematics Special Issue with the same title. All the published papers are of high quality and were subjected to rigorous peer review. Mathematics is included in the Science Citation Index (Web of Science), and its current Impact Factor is 1.747. The papers in this book deal with on R&D performance models, methods for ranking the perspectives and indicators of a balance scorecard, robust optimization model applications, integrated production and distribution problem solving, demand functions, supply chain games, probabilistic optimization and profit research, coordinated techniques for order preference, robustness approaches in bank capital optimization, and hybrid methods for tourism demand forecasting. All the papers included contribute to the development of research.
Keywords: 650; Operational research; Differential equations; Optimization models; Decision theory; Stochastic models; Mathematical models; Management; Measurement models